Pengaruh Media Sosial dalam Mendorong Keputusan Konsumsi Generasi Z di Coffee Shop Kintamani sebagai Wisata Kuliner - Ni Kadek Sri Mirayani; I Gusti Ngurah Oka Widjaya; Ida Bagus Udayana Pidada; Putu Ade Wijana (Lembaga Pengembangan Kinerja Dosen, 2025)
Kintamani is currently viral on social media with the presence of a coffee shop combined with its natural beauty.This study aims to examine the influence of social media on the consumption decisions of Generation Z at coffee shops in the Kintamani area. A quantitative method was employed using a simple linear regression approach. Data were collected through observation, questionnaires and literature studies. The questionnaire was distributed to 50 Generation Z respondents who had visited a coffee shop in Kintamani.The results show that social media has a positive and significant influence on consumption decisions, with a regression coefficient of 0.754 and a significance value of 0.000. The R Square value of 0.672 indicates that 67.2% of the variation in consumption decisions can be explained by social media activity. These findings suggest that social media functions not only as a promotional tool but also as a strategic communication platform that shapes perception and consumer behavior among Generation Z. Therefore, coffee shop businesses are advised to develop engaging, interactive, and relevant social media content to effectively enhance consumption decisions.